Viralité et starisation : le procès Johnny Depp / Amber Heard - Laura Santone (MediAzioni)
This article revisits the trial of Johnny Depp against his ex-wife Amber Heard, a private affair that has been reignited on social networks at an exponential rate. As both protagonists are Hollywood stars, the virality here is questioned not only from a linguistic point of view, but also in the context of the star-system. The analysis is thus developed on two complementary levels: on the one hand, it is based on the notions of PDV (Point of View), empathy, empathic mobility and extimising empathy; on the other, it draws on the « affects », and the imagination, of fans/internet users, for whom the star, as Edgar Morin wrote in the 1970s, « is the fruit of a projection-identification complex of particular virulence ». Throughout the trial, this virulence inevitably leads to virally orchestrated manipulation strategies.